Mammography Equipment - Sa dos Reis, Claudia; Kotre, J. (2015)
Mammography is one of the most technically demanding examinations in radiology, and it requires X-ray technology designed specifically for the task. The pathology to be imaged ranges from small (20–100 μm) high density microcalcifications to ill-defined low contrast masses. These must be imaged against a background of mixed densities. This makes demonstrating pathology challenging. Because of its use in asymptomatic screening, mammography must also employ as low a radiation dose as possible.